Single‐Layer MoS2 Mechanical Resonators. (2nd October 2013) - Castellanos‐Gomez, Andres; van Leeuwen, Ronald; Buscema, Michele; van der Zant, Herre S. J.; Steele, Gary A.; Venstra, Warner J.
<x xml:space="preserve">Abstract</x> Mechanical resonators are fabricated from freely suspended single‐layer MoS2. Their dynamics have been studied by optical interferometry. These resonators behave as membranes with resonance frequencies in between 10 and 30 MHz and quality factors in between 16 and 109. We also demonstrate clear signatures of nonlinear resonance in these atomically thin resonators. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>